Dynamics Modeling and Dynamic Characteristic Analysis of a Spur Gear Pair with Tooth Contact Flash Temperature - Yaping Tian; Lu Xu; Peijie Song; Yandong Chu (Jixie chuandong)
In order to study the influence of the tooth contact flash temperature on the dynamics in the gear system，the tooth contact flash temperature （TCFT） distribution along the line of action of driving gear and driven gear is calculated based on the H.Blok flash temperature theory. The influence of parameters such as speed，load，contact ratio and center distance variation coefficient on TCFT are analyzed. According to Hertz contact theory，the formulas of TCFT and the meshing stiffness，the backlash and the tooth profile error are deduced. A nonlinear dynamics model of a single-stage spur gear system is established when the nonlinear factors such as TCFT，the backlash，the time-varying meshing stiffness and the transmission error are considered. The influences of TCFT on the bifurcation，the tooth surface impact，the take off the meshing and dynamic load coefficient are analyzed by CPNF（Continuous-Poincaré-Newton-Floquet） numerical method in the two-parameter plane pseudo-color mappings. The calculated results show that the load and rotate speed have great influence on TCFT and it reaches the extreme value in entering and exiting the meshing region，therefore，the tooth surface gluing is more likely to happened in here. And，the nonlinear dynamics characteristic of the system are degraded by TCFT. So， TCFT should be controlled.